Valorization of tender coconut mesocarp for the formulation of ready-to-eat dairy-based dessert (Kheer): Utilization of industrial by-product - Bindu Naik; Vijay Kumar; Arun Kumar Gupta (Journal of Agriculture and Food Research, 2023)
The agri-food industry generates a lot of fruit and vegetable processing waste, which opens up a new dimension of research to support zero-waste ideas. These wastes are a good source of bioactive like phytochemicals and dietary fibres that are beneficial to health, but they haven't been used because of a lack of processing technologies. These wastes show a lot of promise as possible functional food ingredients to meet the technological and functional needs that are important for developing health-promoting products with added value. In this study, the goal was to make a ready-to-eat dairy-based dessert (called “kheer”) from blanched coconut mesocarp. First, bioactive and phenolic compounds in the mesocarp were examined. Then, three blanching methods (microwave, boiling water, and steaming) were used to assess the kinetics of the enzymes and inhibit the browning reaction to maintain the sensorial properties of the mesocarp. The effectiveness of each blanching method was assessed by the rapid inactivation of polyphenol oxidase (PPO) and peroxidase (POD). This happened faster in microwaves than in steam or hot water treatment. Based on the kinetic parameters, microwave blanching significantly decreased the enzymatic activity in the mesocarp; as a result, microwave-blanched mesocarp was chosen to make kheer with basmati rice and palm sugar at different concentrations (5–15%). The prepared kheer was evaluated based on sensory parameters, such as its appearance, grain-to-liquid ratio (GLR), consistency, grain texture, sweetness, flavour, and overall acceptability. The results of this study showed that the kheer with 10% tender mesocarp had maximum acceptability. The current study showed that processing tender mesocarp could help turn industrial waste into fiber-rich products that can add economic value to the coconut processing industries.